EPIDEMIOLOGICAL FEATURES OF MELANOMA SKIN CANCER AND SURVIVAL OF ONCOLOGY PATIENTS IN KRASNODAR REGION - S. V. Sharov; R. A. Murashko; L. G. Teslenko; L. L. Stepanova (Кубанский научный медицинский вестник, 2018)
Aim. To assess the effectiveness of preventive, diagnostic and therapeutic work of the oncological service of Krasnodar Region, analyze the epidemiological features of morbidity, mortality, indicators reflecting the diagnosis (the proportion of early detection, neglect) in patients with melanoma skin cancer for the period 2007–2017, and the survival of cancer patients in Krasnodar Region for the period 2007–2016.Materials and methods. Subjects of the study were patients with newly diagnosed melanoma skin cancer in Krasnodar Region for the period 2007–2017. Using an automated information and analytical system the Population Cancer Registry, survival of 3 961 patients with melanoma skin cancer for the period 2007–2016 was analyzed. Standardized rates of morbidity and mortality were calculated according to the accepted world standard with the same age groupings. Statistical processing of data according to the studied indicators was carried out using statistical software packages Statistica. The reliability of the difference in the relative indicators was determined by the t test of the Student, the significance level was adopted as p <0.05.Results. For the period from 2007 to 2017, there has been a significant trend towards an increase in the incidence of melanoma skin cancer of the population of Krasnodar Region. The incidence of melanoma skin cancer in Krasnodar Region is higher than the average for the Russian Federation, which may be due to the presence of an increased level of insolation. During the analyzed period there has been a decrease in the indicator of neglect. With the increase in the stage of melanoma skin cancer, the survival rates both in general among all the diseased and among patients of working age are decreasing. The highest rates of observed and adjusted survival in patients with melanoma skin cancer reduce in the first three years from the date of diagnosis. The indicators of the observed and corrected survival of men of working age with melanoma skin cancer are lower than in women of working age. The indicators of the observed and corrected survival of women of working age with melanoma skin cancer are higher than among the population of all age groups.Сonclusion. The study showed a high level of early diagnosis and quality of treatment for patients with melanoma skin cancer in the Krasnodar Region, as positive trends in the rates of observed and adjusted survival of patients were noted.